Using the Health Belief Model to Explore the Impact of Environmental Empathy on Behavioral Intentions to Protect Ocean Health. Issue 8 (October 2021) - Kim, Sojung Claire; Cooke, Sandra L.
We examine psychological mediating mechanisms to promote ocean health among the U.S. public. Ocean acidification (OA) was chosen as the focus, as experts consider it as important as climate change with the same cause of humanity's excessive carbon dioxide (CO2 ) emissions, but it is lesser known. Empathy is a multi-dimensional concept that includes cognitive and emotional aspects. Previous literature argues that environmental empathy can facilitate positive behaviors. We tested the hypothesis that empathy affects beliefs and behavioral intentions regarding ocean health using the Health Belief Model. We found that higher empathy toward ocean health led to higher perceived susceptibility and severity from OA, greater perceived benefits of CO2 emissions reduction, greater perceived barriers, and keener attention to the media. Beliefs and media attention positively influenced behavioral intentions (e.g., willingness to buy a fuel efficient car). Theoretical and practical implications regarding audience targeting and intervention design are discussed.